ETNOBOTANI TUMBUHAN OBAT MASYARAKAT GAMPONG MAMPLAM ACEH BESAR SEBAGAI ALTERNATIVE PENGGANTI OBAT KIMIA SINTETIK - Safiah, Safiah; Amni, Chairul; Sembiring, Desi Sri Pasca Sari; Andalia, Nurlena (JURNAL ILMIAH EDUNOMIKA, 2024)
Research has been conducted with the title "Ethnobotany of Medicinal Plants by the Gampong Mamplam Aceh Besar Community as a Substitute for Synthetic Chemical Drugs. This study aims to determine the Ethnobotany of Medicinal Plants by the Gampong Mamplam Aceh Besar Community as an Alternative to Chemical Drugs. The research method used is a descriptive method with the location of the research is the entire yard of houses and gardens located in Gampong Mamplam, Leupueng District, Aceh Besar Regency. Data collection is carried out by observation and interviews. The results of the study obtained 14 types of plants found in the village and useful as medicine, 9 types were found to grow a lot in the yard area of the community house while 5 more types grew in the community garden. The parts used are roots, stems, leaves, fruits, herbs, rhizomes, seeds, sap, and bark.